Comparison of neutral and charged polyelectrolyte bottlebrush polymers in dilute salt-free conditions. (2020) - Chremos, Alexandros; Horkay, Ferenc
ABSTRACT: We investigate the structure of neutral and charged bottlebrush polymers in salt-free solutions at different polymer concentrations. In particular, we use molecular dynamics simulations by utilizing a coarse-grained bead-spring model that includes an explicit solvent and complementary experiments made by small angle neutron scattering (SANS). We find that the charged groups along the side chains exert significant repulsive forces, resulting in polymer swelling and backbone stretching. In addition to the primary polyelectrolyte peak, we find that bottlebrush polymers exhibit an additional peak in the form and static structure factors, a feature that is absent in neutral polymers. We show that this additional peak describes the intra-molecular correlations between the charged side chains.